Structural characterization and anti-inflammatory activity of two novel polysaccharides from the sea squirt, Ascidiella aspersa. (October 2016) - Thomson, Derek; Panagos, Charalampos G.; Venkatasamy, Radhakrishnan; Moss, Claire; Robinson, Joanne; Bavington, Charles D.; Hogwood, John; Mulloy, Barbara; Uhrín, Dušan; Spina, Domenico; Page, Clive P.
Abstract: It is now recognized that certain polysaccharides can exhibit anti-inflammatory activity, including the glycosaminoglycan (GAG) heparin that is widely used as an anti-coagulant drug. However, it would be desirable to identify molecules that retain the anti-inflammatory actions of heparin, but that are devoid of significant anti-coagulant activity. In the present study we have identified a number of novel GAG and GAG-like polysaccharides (VRP327) from marine organisms, most of which were resistant to digestion by heparinase II and chondroitinase ABC. Fourier transform infra-red spectrum (FTIR) revealed species with variable degrees of sulphation and monosaccharide analysis revealed a range of sugar compounds, which in some cases included sugars not present in mammalian GAGs. 1 H NMR spectra of these species are consistent with the structures of complex polysaccharides. From an initial screening cascade to remove compounds having significant anti-coagulant activity and no overt cytotoxicity, we identified a high molecular weight oversulphated dermatan sulphate (VRP327) isolated from the tunicate Ascidiella aspersa which was fully characterised by NMR spectroscopy. This material was depolymerised to produce well characterized low molecular weight fractions which were demonstrated to be non-toxic, with low levels of anti-coagulant activity, and to have demonstrable anti-inflammatory activity assessed in several in vitro and in vivo models. The identification of low molecular weight polysaccharides having significant anti-inflammatory activity without significant anti-coagulant activity may provide novel templates for the development of a novel class of anti-inflammatory drugs.